Bridging the Gap: Exploring the Relationship between Information Access and Environmental Justice in Library Practices - Durodolu, Oluwole; Oladokun, Bolaji (Folia Toruniensia, 2024)
Aims: The intersection of information access and environmental justice has become increasingly vital as communities worldwide grapple with environmental challenges. This study explores the relationship between information access and environmental justice in library practices, focusing on academic librarians at the Federal University of Technology Ikot Abasi in Nigeria’s Niger Delta region. Methods: This study utilized a descriptive design. The study involved six academic librarians from the Federal University of Technology, Ikot Abasi, Akwa Ibom State of Nigeria, selected for their expertise in facilitating information access and availability especially as it relates to the roles of libraries in environmental justice initiatives within academia. Data were gathered through focus group discussions (FGDs) with the participating librarians, conducted in a conducive and private setting to encourage open dialogue and diverse perspectives. Thematic analysis was employed to analyze the FGD transcripts. Results: The findings emphasize the importance of multilingual resources, targeted outreach, translation services, collaboration with community leaders, consideration of literacy levels, and cultural relevance in ensuring information accessibility. Challenges such as limited internet access, language barriers, disparities in digital literacy, lack of awareness, and resistance from certain community members hinder equitable information access. Conclusion: The study concludes that librarians contribute to environmental justice advocacy through participation in local initiatives, policy engagement, awareness raising, and collaboration with stakeholders. This study sheds light on the crucial role of libraries in advancing environmental justice and suggests strategies for enhancing information access and advocacy efforts in the pursuit of sustainable development agendas.